2022
DOI: 10.1111/1759-3441.12332
|View full text |Cite
|
Sign up to set email alerts
|

Information Communication Technologies, Globalisation and Growth: Evidence from the ASEAN Economies*

Abstract: This study examines the impact of information and communication technologies (ICT) and globalisation on economic growth in the (Association of South-East Asian) ASEAN economies from 1999 to 2019 using dynamic panel estimators. Previous literature has shown that ICT and globalisation can impact growth through the role of knowledge dissemination and information. Subsequently, this study examines the moderating impact of globalisation on the relationship between ICT and economic growth. Our results show that both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…On the empirical front, Kabuga and Ismail (2018) and Das and Paul (2011) found that trade openness stimulates the economic growth of 12 Emerging Asian economies. Haini and Wei Loon (2022) and Haini and Loon (2021) confirm these findings for ASEAN and OECD economies where trade induces economic growth. Similarly, Malefane and Odhiambo (2018) found a positive impact of trade openness on economic growth in South Africa, but the effect turns insignificant when geography and country size are considered.…”
Section: Trade Openness and Economic Growthsupporting
confidence: 69%
“…On the empirical front, Kabuga and Ismail (2018) and Das and Paul (2011) found that trade openness stimulates the economic growth of 12 Emerging Asian economies. Haini and Wei Loon (2022) and Haini and Loon (2021) confirm these findings for ASEAN and OECD economies where trade induces economic growth. Similarly, Malefane and Odhiambo (2018) found a positive impact of trade openness on economic growth in South Africa, but the effect turns insignificant when geography and country size are considered.…”
Section: Trade Openness and Economic Growthsupporting
confidence: 69%
“…As a result, ICT creates value added at the firm and sectoral level and thus leads to improved productivity and economic growth at the country level (Aghaei & Rezagholizadeh, 2017; Pradhan et al, 2018; Quah, 2002). Also, ICT can benefit the economy directly by reducing transaction costs and indirectly by speeding up information flows (Niebel, 2018), while globalization allows firms to compete globally, increasing their incentives to obtain information and potentially realize greater profits on a large scale (Grossman & Helpman, 2015; Haini & Wei Loon, 2022). On the other hand, the development of the ICT sector can foster network effects and knowledge enrichment, which can further promote the positive spillovers of globalization, in addition to reducing transaction costs while increasing information transmission (Edquist et al, 2018; Haini, 2021; Vu, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The literature has shown that information and communications technology, particularly with the onset of the Internet, can benefit the economy by directly lowering transaction costs and indirectly by accelerating informational flows that affect growth endogenously (Niebel, 2018). Additionally, direct investment into the information technology sector such as the Internet, involves large capital investments that affect growth directly via the production function (Haini & Wei Loon, 2022).…”
Section: Discussionmentioning
confidence: 99%